Nanotechnology and azo-dyes in sweets - Staudinger, M.; Punz, E.; Joubert, I.A.; Himly, M.; Geppert, M. (Open Schools Journal for Open Science, 2020)
Nanotechnology is a fast growing field and conseidere as a key-technology of the 21st century. Nanoparticles are not only used in high-tech products or medical devices but are also more and more incorporated in food producrs, for example in sweets. In addtion, for food-coloring, azo-dyes are frequetly used which makes an encounter of azo-dyes and nanoparticles unavidable, The aim of this work was the isolation and characterisaton of these dyes without including nanoparticles in a selected sweet product.